2013
DOI: 10.3762/bjoc.9.315
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric epoxide–amine adducts based on 2-amino-N-isopropylacetamide and α-amino-ε-caprolactam: Solubility in presence of cyclodextrin and curing properties

Abstract: Summary2-Amino-N-isopropylacetamide and α-amino-ε-caprolactam were reacted with glycerol diglycidyl ether to give novel oligomeric thermoresponsive epoxide–amine adducts. These oligomers exhibit a lower critical solution temperature (LCST) behavior in water. The solubility properties were influenced with randomly methylated β-cyclodextrin (RAMEB-CD) and the curing properties of the amine–epoxide mixtures were analyzed by oscillatory rheology and differential scanning calorimetry, whereby significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The T C of a thermoresponsive polymer solution can be altered easily by variation of the chemical structure and to a certain degree by variation of the chain length of the used polymer, also. Interestingly, the T C -values of suitable polymers in water can also be influenced significantly by supramolecular interactions with cyclodextrin [ 9 ]. Accordingly, we described in 2003 for the first time, that the LCST of a poly( N -adamantylacrylamide-co- N ’-isopropylacrylamide) is influenced by CD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The T C of a thermoresponsive polymer solution can be altered easily by variation of the chemical structure and to a certain degree by variation of the chain length of the used polymer, also. Interestingly, the T C -values of suitable polymers in water can also be influenced significantly by supramolecular interactions with cyclodextrin [ 9 ]. Accordingly, we described in 2003 for the first time, that the LCST of a poly( N -adamantylacrylamide-co- N ’-isopropylacrylamide) is influenced by CD [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The band at 1236 and 1082 cm − 1 are characteristic for C\ \O\ \C cyclic and acyclic groups of epoxy present in DGEBA, respectively [81]. In addition, the band at 838 cm −1 confirmed the characteristic asymmetric vibration of epoxide ring [82]. The band at 1141 cm −1 in all spectra ascertained the existence of C\ \O bond in PVA.…”
Section: Ftir Analysismentioning
confidence: 65%
“…In particular, the absorption bands corresponding to the vibrations of carboxyl and epoxy groups are of special interest to evaluate the extent of reactions in the investigated system. In fact, from Figure 7 , it can be observed that in the EA prepolymer, the intensity of the IR absorption bands arising from –C–H (3057 cm −1 ), C–O (914 cm −1 ), and C–O–C (825 cm −1 ) stretching vibrations of oxirane groups [ 31 , 32 , 33 ] decrease, thus confirming that the ring-opening of epoxy groups took place. Furthermore, one can note that the peak at 1695 cm −1 originating from the carbonyl stretching mode in AA [ 34 , 35 ] becomes less intense as a result of the reaction and finally indistinguishable.…”
Section: Resultsmentioning
confidence: 88%